A novel MMP-responsive nanoplatform with transformable magnetic resonance property for quantitative tumor bioimaging and synergetic chemo-photothermal therapy. (August 2022) - Chen, An; Lu, Hongwei; Cao, Rong; Zhu, Yi; Li, Yumeng; Ge, Renbin; Zhang, Siruo; Li, Yulin; Xiao, Lan; Su, Li; Zhao, Jinhua; Hu, Honggang; et al.
Abstract: Quantifying bio-targeted markers in the tumor microenvironment through non-invasive approaches remains challenging. In this study, a novel matrix metalloproteinase-9 (MMP9) responsive nanoplatform (PMP@USPIO/DOX, PMPSD) with transformable magnetic resonance property is designed for quantitative tumor bioimaging and synergetic chemo-photothermal therapy. The nanoplatform acts as a T2 contrast agent in physiological conditions due to the ultrasmall superparamagnetic iron oxide (USPIO) aggregation state, whereas in the tumor microenvironment, the nanoclusters are dissociated by MMP9, thus transforming the nanoplatform into a T1 contrast agent. T1 &T2 weighted image and T1 &T2 maps are utilized to quantitatively study the correlation between MRI signal changes and MMP9 concentrations and to evaluate MMP9 activity. In addition, the PMP@USPIO/DOX nanoplatform possesses excellent photothermal properties. PMPSD combined with laser irradiation is more effective than single chemo-/photothermal therapy, and up-regulation of the MMP9 level in the tumor can further improve the therapeutic effect. The nanoplatform is of great significance in evaluating disease prognosis and non-invasive monitoring of drug release. The concept reported here provides a creative idea for the non-invasive quantitative study of the tumor microenvironment. Graphical Abstract: ga1 Highlights: Quantifying bio-targeted markers in the tumor microenvironment through non-invasive approaches is of great significance for cancer. R1 &R2 values were utilized to quantify MMP9 concentrations and evaluate MMP9 activity. The nanoplatform is of great significance in evaluating disease prognosis and non-invasive monitoring of drug release.